2013
DOI: 10.1016/j.archoralbio.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Tooth agenesis patterns in unilateral cleft lip and palate in humans

Abstract: A higher prevalence of tooth agenesis is observed in patients with CUCLP, even outside the cleft region, compared with the general population. Thirteen different patterns were observed, of which 6 were unique patterns. Certain teeth were involved in all agenesis patterns. Both the prevalence of orofacial clefting as well as hypodontia is more frequently observed on the left side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 35 publications
4
62
0
4
Order By: Relevance
“…These results are in concordance with other research reports [14]. Still, the majority of the patients belonged to the CL + P L group (38.3%) in agreement with relative research investigations [9, 15, 20]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in concordance with other research reports [14]. Still, the majority of the patients belonged to the CL + P L group (38.3%) in agreement with relative research investigations [9, 15, 20]. …”
Section: Discussionsupporting
confidence: 93%
“…Additionally, dental anomalies appear more commonly in the cleft rather than the non-cleft area [4, 10, 1214]. It is reported that the prevalence of left-sided clefts is higher than right-sided clefts; the cause still remaining unknown [9, 15]. Data from the literature indicate that isolated cleft lip patients (CL) seem to be less affected by dental anomalies outside the cleft area compared to CP or CL + P patients [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The congenital absence of teeth was determined by clinical and radiographic examination using orthopantomogram (OPG). According to the number of missing teeth, subjects were subdivided into three groups: group A -mild (1-2), group Bmoderate (3)(4)(5)(6), and group C -severe (≥7 congenitally missing permanent teeth). The number and average ages of the study groups are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of hypodontia in the general population varies from 2.3% to 10.1% (excluding third molars). [2][3][4][5] Hypodontia can be associated with a cleft lip and palate, 6,7 and with more than 50 syndromes, 8,9 or may present as an isolated entity. 10,11 Oligodontia is rarer condition and its prevalence in the permanent dentition is between 0.15% and 0.45%.…”
Section: Introductionmentioning
confidence: 99%